The effect of interface properties on the adhesion of cement paste to various substrates. - Pye, Glendon B. (University of Ottawa (Canada), 1990)
This study deals with the adhesion of cement paste and modified cement paste systems to substrates of steel and glass for hydration times of up to seven days. The bond strength of cement, clinker and C$\sb3$S paste in addition to cement paste systems containing salts (NaNO$\sb3$, CaCl$\sb2$, Ca(C$\sb3$H$\sb5$O$\sb2$)$\sb2$.H$\sb2$O) and silica fume was studied using a uniaxial tensile testing apparatus. A new term, interface fracture energy, was derived to provide a more meaningful basis for comparison of bond tests. This was necessary as the interfacial bond for all the paste systems was thickness dependent. A decrease in paste thickness resulted in an increase in bond failure stress. Factors other than the deposition of CH and C-S-H at the interface may affect bond strength. Comparison of the bond strength data for the control paste and the C$\sb3$S and clinker pastes indicates that the effect of the hydration products resulting from gypsum reactions eg. sulphoaluminate phases, may be secondary. Physico-mechanical characteristics of the interface eg. geometry and size of inherent flaws may be important. The addition of the salts and silica fume did not consistantly increase the bond strength of the paste. It is inferred that factors other than CH crystal size are important. Interface fracture energy, $\gamma$, reaches a maximum after one day, decreases at two days then remains relatively constant. The decrease in bond strength may be due to the pressure exerted by the formation of CH crystals in the interface. In general the interface fracture energy increased with a decrease in water-cement ratio. Other time and system dependent factors appear to affect the development of interface fracture energy. Values of $\gamma$ for all systems studied range from 0.001 to 1.66 Jm$\sp{-2}$ suggesting that van der Waal's forces of attraction are the primary binding forces.
Keywords: Engineering, Civil.